MENINGKATKAN KEMAMPUAN GURU KELAS VI DALAM PEMBELAJARAN MATEMATIKA MELALUI SUPERVISI AKADEMIK DI SD - Rismaida Rismaida (Manajer Pendididikan, 2017)
The background of this study carry out academic supervision in elementary schools, the academic supervision of teacher is important because it affects the level of ability of teachers. Based on this, of course, the competence of teachers in teaching is very influential, especially in improving the creativity of student learning. Through Action Research School (PTS) is the principal can improve the way teachers teach in the classroom. In underlying the above background, the authors sought to improve the ability of classroom teachers in mathematics learning through academic supervision. The results showed that the ability to carry out classroom teachers improve the academic supervision